Recreational Drug Consumption An Economic Perspective - Ramful Srivastava, Pratima; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2013)
Recreational drug policies and regulations are complex issues with many dimensions. This book attempts to answer several questions raised in current drug policy debates. Developing cost-effective drug programs and policies require a sound knowledge of drug users and their characteristics and the relationship across drugs. Who are the drug users? Can demographic factors help towards predicting drug usage? What sub-population groups should be targeted for drug campaigns and educational programs? Can a drug policy aimed at discouraging the use of one drug likely affect the use of other drugs which are its economic substitutes or complements? What are the implications of drug use? Policymakers and researchers in the area of health and social development would find this book very useful.
Introduction -- Literature Review -- An Overview of Recreational Drug Consumption in Australia -- Modelling Consumption of Individual Drugs -- Modelling Multiple Drug Use using a Multivariate Approach -- Modelling Alcohol Consumption by Levels using an Ordered Generalised Extreme Value (OGEV) Model -- Drinking Patterns and Earnings -- Summary, Policy Implications and Further Research.
Keywords: Economics; Medicine; Social policy; Economics/Management Science; Health Economics; Social Policy; Health Promotion and Disease Prevention